ToughLove : raising confident, kind, resilient kids - Gottlieb, Lori; Stiepock, Lisa; Drexler, Peggy; Mac Kenzie, Robert J.; Ginsburg, Kenneth R.; Levine, Madeline; Walfish, Fran; Galinsky, Ellen; Corwin, Ann; Kenney, Lynne; Castle, Jill, 1966-; Taylor, Jim; et al. (Simon & Schuster Paperbacks, 2016)
"Combining a high level of nurture with an emphasis on boundaries and structure, toughLOVE is the sanity-saving guide to raising school-age children who will be kind, confident adults. Our eighteen leading experts help you find solutions that come from decades in the trenches as the country's most esteemed and well-known coaches, therapists, teachers, and counselors. And, perhaps most significantly, as parents themselves,"--page [4] of cover.